Characterization of Cu-Sn-In thin films for three-dimensional heterogeneous system integration - Sasangka, Wardhana Aji (2014)
Cu/Sn-In solder thin films were studied as a low temperature bonding material for 3D heterogeneous system integration. A new technique based on observation of color changes and combinatorial deposition of solder thin films was developed to investigate the intermetallic compound (IMC) growth kinetics in Cu/Sn and Cu/SnxIn100-x bilayer systems. A general model for IMC growth kinetics in these systems was developed and was found to be in close agreement with experimental data. The model considers the diffusive flux of Cu and Sn through the IMC layer and the reaction fluxes of Cu and Sn atoms at the Cu/IMC and IMC/Sn interfaces. It was observed that IMC growth is controlled by the rate of reaction between Cu and Sn for thin IMCs. On the other hand, Cu diffusion along IMC grain boundaries and Sn diffusion through the IMC lattice is the rate limiting step for thick IMCs at low and high temperatures, respectively. It was also discovered that an addition of 44% In into Sn solder leads to the fastest IMC growth in Cu/SnxIn100-x bilayer films. Microcantilevers coupled with combinatorial deposition were used to characterize the residual stress, Young's modulus and fracture strength of Cu-Sn-In thin films. Measurement inaccuracies due to cantilever non-idealities were corrected using finite element simulations and deflection measurements at multiple locations. It was discovered that an alloy with 46% In in Sn resulted in an IMC with the highest fracture strength. The findings of this study demonstrate the potential of Sn-In solder in lowering the bonding temperature and increasing the fracture strength of the resulting IMC. Moreover, the techniques developed in this study provide a highly efficient general approach for finding solder compositions that allow the fastest and/or slowest IMC growth rate, as well as the most desirable mechanical properties.